The ‘Ulama and Islamic Renaissance in Algeria (American Journal of Islam and Society, 1989)
IntroductionThis work is concerned primarily with the activities of the Algerian ‘Ulamain the social and religious field. The most organized activities of Islamicreformism in Algeria started in 1931 with the establishment of the Associationof the Algerian ‘Ulama. The ‘Ulama declared the ultimate goal of theirAssociation to be only religious and cultural. The subsequent Islamicrenaissance which they instituted in Algeria concentrated on the independenceof the Muslim Creed, and social and cultural revivalism. The objective wasto reform the practice of Islamic religion along the lines of the Islam of Suhjiyuhand not the Islam of Sufi sects. This was pursued by attacking the negativeaspects of a1 vzwiiyuh (Sufi centers) and by encouraging the spread of altu‘lim al hurr (the ‘Ulama type of education).The most significant role of al buthal dini (religious reformism) wasthat it ventured to prepare the Algerian masses for the violent conflict withFrance. Had it not been for this movement, the Algerian masses would haveremained under the influence of the saints whose followers supported andconsolidated the French colonial administration. In the following pages, thequestion will be posed as to how the liberation of Algeria was facilitatedby the Algerian religious renaissance, which managed to liberate the consciousnessof the masses. As a result, the Algerian masses were preparedmorally and psychologically for political liberation from France.The Origins of Islamic Renaissance In AlgeriaThe origins of the Islamic renaissance in Algeria were directly linkedto the Suluflyuh movement, which flourished in ul Mushriq al Arubi during ...